(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
MSME in Kembangan Selatan Urban Village face obstacles in tax compliance and financial management, which have an impact on business credibility. This activity aims to increase MSME players’ understanding of the importance of tax compliance and bookkeeping for professional business development. The implementation includes interactive training (workshops) and technical assistance, with materials covering NPWP registration, final income tax calculation, simple bookkeeping based on SAK EMKM, and legality-based branding strategies. A total of 35 MSME players participated in the activities held on February 26, 2025. Evaluation showed significant improvements: (1) 70% of participants already had NPWP (previously 0%), (2) 80% understood tax obligations (up from 20%), (3) 60% were able to prepare monthly financial reports (previously 10%) and (4) 50% of MSME adopted structured branding strategies. The average score of the participant satisfaction questionnaire reached 3.63 (scale 4). Outputs include video documentation, training modules, publication on Kompasiana, and IPR submission. The program successfully increased the capacity of MSMEs in taxation and financial aspects. A collaborative approach between academics, local governments, and businesses proved effective in accelerating the formalization of MSME.